A case study on the acquisition of plurality in a bilingual Malay-English context-bound child - Rabiah Tul Adawiyah Mohamed Salleh,; Kawaguchi, Satomi; Biase, Bruno Di (Penerbit Universiti Kebangsaan Malaysia, 2019)
The early development of simultaneous bilinguals has been at the core of heated controversy since the mid-seventies. The Unitary Language System Hypothesis by Volterra and Taeschner saw early development as a single language system gradually diverging into two systems. On the contrary, Meisel (1989), De Houwer (1990) and Paradis and Genesee (1996) suggested the early separation of two linguistic systems. Neither position, however, considered language environmental conditions constraining development as key variables. This paper aims to show that the predominant environmental languages to which the Malay- English bilingual child in the current study was alternately exposed might have played an important role in shaping the child’s acquisition of plurality in each language. Throughout the period of investigation (from age 3;4 to 3;10 and at 4;8) the child’s interactions were regularly audio and video recorded. The current study focuses on the development of plural marking in a simultaneous Malay-English bilingual child. Interestingly, at a point when English was environmentally predominant, the child would occasionally use the English plural suffix -s on Malay nouns. After moving back to Malaysia, the child used reduplication to mark plurals in both languages. The findings of this study indicate that the predominant linguistic environment in which the child grows and develops plays an important role in shaping the child’s language production.